The Effect of Environmental Contexts from Ecological Perspective on Motor Development and Creativity of Children - Kosar Abbaspour (Alzahra University, 2021)
The purpose of this study was to investigate the effect of environmental contexts from ecological perspective on motor development and creativity of children. For this purpose, the semi-experimental method with pre-test and post-test design was used with the purposive sampling method. This study included preschool children aged 4.5 to 6.5 years who were divided into two groups of 15 people based on differences in environmental contexts. The first group were children who were in the natural space (nature school) and the second group were children who were indoors space (kindergarten). Both groups conducted their activities in the specified environments for two months. To measure motor development (gross motor skill) was used the Bruininks-oseretsky Test of Motor Proficiency and for children's creativity was used the Torrance Test of Creativity Thinking. Results of mixed ANOVA showed that gross motor skill of children in the natural space are more improved than indoor space. Also activity in outdoor space had positive and significant effect on the all five factors of creativity (fluency, flexibility, originality, elaboration and total creativity skill) of children. Therefore, it can be concluded that the natural environment improves the motor skills development and creativity of children more than the indoor environment and it is suggested to use environmental variability, especially the natural environment for preschoolers.